Serpentinization-Driven H2 Production From Continental Break-Up to Mid-Ocean Ridge Spreading: Unexpected High Rates at the West Iberia Margin - Albers, Elmar; Bach, Wolfgang; Pérez-Gussinyé, Marta; McCammon, Catherine; Frederichs, Thomas (Frontiers in Earth Science, 2021)
Molecular hydrogen (H2) released during serpentinization of mantle rocks is one of the main fuels for chemosynthetic life. Processes of H2 production at slow-spreading mid-ocean ridges (MORs) have received much attention in the past. Less well understood is serpentinization at passive continental margins where different rock types are involved (lherzolite instead of harzburgite/dunite at MORs) and the alteration temperatures tend to be lower (<200°C vs. >200°C). To help closing this knowledge gap we investigated drill core samples from the West Iberia margin. Lherzolitic compositions and spinel geochemistry indicate that the exhumed peridotites resemble sub-continental lithospheric mantle. The rocks are strongly serpentinized, mainly consist of serpentine with little magnetite, and are generally brucite-free. Serpentine can be uncommonly Fe-rich, with XMg = Mg/(Mg+Fe) < 0.8, and shows distinct compositional trends towards a cronstedtite endmember. Bulk rock and silicate fraction Fe(III)/∑Fe ratios are 0.6–0.92 and 0.58–0.8, respectively; our data show that 2/3 of the ferric Fe is accounted for by Fe(III)-serpentine. Mass balance and thermodynamic calculations suggest that the sample’s initial serpentinization produced ~120 to >300 mmol H2 per kg rock. The cold, late-stage weathering of the serpentinites at the seafloor caused additional H2 formation. These results suggest that the H2 generation potential evolves during the transition from continental break-up to ultraslow and, eventually, slow MOR spreading. Metamorphic phase assemblages systematically vary between these settings, which has consequences for H2 yields during serpentinization. At magma-poor rifted margins and ultraslow-spreading MORs, serpentine hosts most Fe(III). Hydrogen yields of 120 to >300 mmol and 50–150 mmol H2 per kg rock, respectively, may be expected at temperatures of <200°C. At slow-spreading MORs, in contrast, serpentinization may produce 200–350 mmol H2, most of which is related to magnetite formation at >200°C. Since in comparison to slow-spreading MORs, however, geothermal gradients at magma-poor margins and ultraslow-spreading MORs are lower, larger volumes of low-temperature serpentinite should form in these settings. Serpentinization of lherzolitic rocks at magma-poor margins should produce particularly high amounts of H2 under conditions within the habitable zone. Passive margins may hence be more relevant environments for hydrogenotrophic microbial life than previously thought.